The Running Dream - Van Draanen, Wendelin (New York : Alfred A. Knopf, 2011)
When a school bus accident leaves sixteen-year-old Jessica an amputee, she returns to school with a prosthetic limb and her track team finds a wonderful way to help rekindle her dream of running again.
Keywords: Running -- Fiction; Artificial limbs -- Fiction; Handicapped -- Fiction; High schools -- Fiction; School stories